The newspaper press directory and advertisers guide, 1951 - Archive CD Books Australia (London : Benn Brothers, 1951)
Lists thousands of different newspapers, magazines and periodicals from the British Isles and its colonies.
"A facsimile Reproduction of the Original Book"
"Quality scans by Bookeye"
System requirements: This CD-ROM can be viewed by any computer using Adobe Acrobat Reader 4 or later. Adobe Reader 6 or later is recommended
Keywords: Press -- Great Britain -- Directories; Press -- Ireland -- Directories; Press -- Directories; Newspapers -- Directories; Newspapers -- Great Britain -- Directories; Newspapers -- Ireland -- Directories; Periodicals -- Great Britain -- Directories; Periodicals -- Directories